WHEN RELIGIOUS JUDGES PROTECT CHILDREN'S RIGHTS: Case of Divorce in Padangsidempuan Religious Court - Ahmatnijar, Ahmatnijar; Tenrilawa, Dian Furqani; Asmuni, Asmuni; Matsum, Hasan; Subha, Rahman (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
In a marriage, a parent is the primary party that fulfills children's rights, but in reality, not all marriages end in ideal conditions. In many divorces, children's rights are jeopardized. This paper aims to study how children's rights are fulfilled at the hands of the Padangsidimpuan Religious Courts. Data for this study were collected through in-depth interviews, while secondary data was obtained from the case register files at the Padangsidimpuan Religious Court. After conducting research, it was found that the majority of wives who filed for divorce at the Padangsidimpuan Religious Court mostly did not include the rights of the children in their petition. In deciding this case, the judge at the Padangsidimpuan Religious Court followed existing regulations. The verdict always refers to the posita. However, apart from that, many judges also advise the litigants to include children's rights in the posita lawsuit therefore their rights can be protected by a judge's decision.[Dalam sebuah perkawinan, orang tua seharusnya menjadi pihak utama yang memenuhi hak-hak anak, tetapi ternyata tidak semua pernikahan baik-baik saja. Banyak terjadi perceraian yang mengancam hak anak. Tulisan ini bertujuan untuk mengkaji bagaimana terpenuhinya hak-hak anak di Pengadilan Agama. Data dalam penelitian ini dikumpulkan dengan cara melakukan wawancra mendalam, sedangkan data sekunder diperoleh dari berkas-berkar register perkara di Pengadilan Agama Padangsidimpuan. Setelah melakukan penelitian didapatkan fakta bahwa mayoritas istri yang mengajukan gugatan cerai di Pengadilan Agama Padangsidimpuan hanya mengajukan gugat cerai belaka tanpa turut menyertakan hak anak yang di bawah pengasuhannya.Hakim Pengadilan Agama Padangsidimpuan dalam memutuskan hal tersebut konsisten dengan regulasi yang ada. Putusan selalu merujuk posita. Namun ternyata selain itu, banyak juga hakim yang menyarankan kepada pihak yang berperkara untuk memasukkan hak-hak anak dalam posita gugatan agar dapat dilindungi haknya oleh putusan hakim.]